Antiproliferative Effects of Roylea cinerea (D. Don) Baillon Leaves in Immortalized L6 Rat Skeletal Muscle Cell Line: Role of Reactive Oxygen Species Mediated Pathway - Bhatia, Astha; Singh Buttar, Harpal; Arora, Rohit; Singh, Balbir; Singh, Amritpal; Kaur, Sarabjit; Arora, Saroj (Frontiers in Pharmacology, 2020)
Roylea cinerea (D. Don) Baill. (Lamiaceae) is an indigenous plant of Western Himalayas, and has been used by the native population for the treatment of various diseases such as fever, malaria, diabetes, jaundice, and skin ailments etc. However, limited proportion of pharmacological and toxicological information is available on the bioactive properties of this plant. Therefore, the present study was designed to explore the anti-oxidant and anti-proliferative activities Roylea cinerea. Methanolic extracts of leaves and stem of Roylea cinerea were prepared through maceration procedure and evaluated for the antioxidant activity using hydrogen/electron donating and hydroxyl radical scavenging assay. Significant antioxidant activity was observed for the methanolic extract of leaves in DPPH (EC50 239 µg/mL), molybdate ion reduction assay (29.73 µg ascorbic acid equivalent/mg dry weight of extract) as well as in plasmid nicking assay. Anti-proliferative and apoptotic activity in L6 rat skeletal muscle cell line was done using in vitro assays, i.e. MTT, Lactate dehydrogenase, mitochondrial membrane potential assay along with phase contrast, confocal and scanning electron microscopy. The methanol extract of leaves and stem inhibited the growth of L6 cells with IC50 value of 69.41µg/mL and 124.93 µg/mL ,respectively, and the lactate dehydrogenase activity was 20.29 % and 0.3%, respectively. Cell cycle analysis by flow cytometry exhibited the arrest of cells in G1 and sub-G1 phase by methanolic leaves extract. Furthermore, the results of microscopic and docking analysis strengthened the observation made in the present study regarding the apoptotic mode of cell death in the L6 cell line. The in vitro findings of our studies reveal that the bioactive ingredients present in the methanolic extract of leaves and stem of Roylea cinerea have the anticancer potential. Further in vivo studies are needed to verify the in vitro results.